2010
DOI: 10.1111/j.1469-8986.2010.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing that leads to conscious perception: A unique window to central auditory processing opened by the mismatch negativity and related responses

Abstract: In this review, we will present a model of brain events leading to conscious perception in audition. This represents an updated version of Näätänen's previous model of automatic and attentive central auditory processing. This revised model is mainly based on the mismatch negativity (MMN) and N1 indices of automatic processing, the processing negativity (PN) index of selective attention, and their magnetoencephalographic (MEG) and functional magnetic resonance imaging (fMRI) equivalents. Special attention is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
326
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(344 citation statements)
references
References 311 publications
(429 reference statements)
14
326
4
Order By: Relevance
“…For time window 90-160 ms, the 3 (Deviant type: EP, E, and P) 9 3 (Region: frontal, central, and parietal) 9 3 (Hemisphere: left, middle, and right) repeated ANOVA reveals a significant main effect for Deviant type, F (2, 52) = 11.55, p \ .01, g p 2 = .31, demonstrating that the difference waveform evoked by deviants in the EP condition [Mean Amplitudes (MA = -1.85 lV)] was more negative (p = .07, marginally significantly) than that in the E condition (MA = -1.05 lV); and in turn more negative than that in the P condition (MA = -0.14 lV) significantly (p \ .05). The main effect on the brain region was also significant, F (2, 52) = 7.53, p \ .01, g p 2 = .22, and a typical fronto-central distributed pattern of mismatch negative waveform was observed (Müller et al 2002;Näätänen et al 2010). Brain responses were more negative in the frontal and central than in the parietal region (ps \ .05); no difference between the frontal and central regions was observed (p [ .1).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…For time window 90-160 ms, the 3 (Deviant type: EP, E, and P) 9 3 (Region: frontal, central, and parietal) 9 3 (Hemisphere: left, middle, and right) repeated ANOVA reveals a significant main effect for Deviant type, F (2, 52) = 11.55, p \ .01, g p 2 = .31, demonstrating that the difference waveform evoked by deviants in the EP condition [Mean Amplitudes (MA = -1.85 lV)] was more negative (p = .07, marginally significantly) than that in the E condition (MA = -1.05 lV); and in turn more negative than that in the P condition (MA = -0.14 lV) significantly (p \ .05). The main effect on the brain region was also significant, F (2, 52) = 7.53, p \ .01, g p 2 = .22, and a typical fronto-central distributed pattern of mismatch negative waveform was observed (Müller et al 2002;Näätänen et al 2010). Brain responses were more negative in the frontal and central than in the parietal region (ps \ .05); no difference between the frontal and central regions was observed (p [ .1).…”
Section: Resultsmentioning
confidence: 82%
“…In this paradigm, participants are exposed to a stream of consecutive sounds that contain repeated standard stimuli and infrequent deviant stimuli, from different emotional categories, and required to perform a stimulus-unrelated task (e.g., watching a silent movie). Mismatch negativity (MMN), obtained by subtracting the brain responses to physically identical standards from those to occasional deviants, is considered to be associated with the involuntary attention switch caused by auditory changes (Näätänen et al 2007(Näätänen et al , 2010. In the studies on emotional prosody, brain responses to repeated standard stimuli are compared with responses to deviant stimuli from different emotional categories.…”
Section: Introductionmentioning
confidence: 99%
“…MMN indicates that an auditory input differs from predicted causes and signals the need for two related actions: firstly, the model has proven inaccurate and therefore requires updating (Winkler et al 1996;Winkler 2007), and second, the environment has changed in some way that might require a change in ongoing behaviour (Näätänen 1990;Schröger 1997;Näätänen et al 2011). The former action is indicated by research demonstrating that activity contributing to MMN is dependent on what model(s) the auditory system possesses at the time the deviant is encountered as opposed to the characteristics of the deviant itself (see Winkler et al 1996;Winkler and Czigler, 1998).…”
Section: Mismatch Negativitymentioning
confidence: 99%
“…The former action is indicated by research demonstrating that activity contributing to MMN is dependent on what model(s) the auditory system possesses at the time the deviant is encountered as opposed to the characteristics of the deviant itself (see Winkler et al 1996;Winkler and Czigler, 1998). The latter action reflects an interpretation of MMN as part of a relevance filtering process that operates as the first stage in an orienting response to the deviating event (Escera et al 2000;Friston 2005, Näätänen et al 2011.…”
Section: Mismatch Negativitymentioning
confidence: 99%
“…A large number of auditory-evoked potential (AEP) studies in humans indicate that infrequently occurring deviant sounds reliably elicit a negative cortical EEG potential at 100 -200 ms from change onset, named the mismatch negativity (MMN; Näätänen et al, 2011). Recent animal results from single-unit recordings in the primary auditory cortex , the thalamus (Kraus et al, 1994;Antunes et al, 2010), and the inferior colliculus (Malmierca et al, 2009) have suggested, however, that the MMN might be preceded by much earlier (20 -40 ms) auditory novelty-related activity.…”
Section: Introductionmentioning
confidence: 99%